Values and Valuing in Mathematics Education Scanning and Scoping the Territory - Clarkson, Philip; Seah, Wee Tiong; Pang, JeongSuk (ICME-13 Monographs, 2019)
This engaging open access book discusses how a values and valuing perspective can facilitate a more effective mathematics pedagogical experience, and allows readers to explore multiple applications of the values perspective across different education systems. It also clearly shows that teaching mathematics involves not only reasoning and feelings, but also students' interactions with their cultural setting and each other. The book brings together the work of world leaders and new thinkers in mathematics educational research to improve the learning and teaching of mathematics. Addressing themes such as discovering hidden cultural values, a multicultural society and methodological issues in the investigation of values in mathematics, it stimulates readers to consider these topics in cross-cultural ways, and offers suggestions for research and classroom practice. It is a valuable resource for scholars of mathematics education, from early childhood through to higher education and an inspiring read for all mathematics teachers. ; Features the intellectual work of researchers from different ethnicities and nationalities Offers an alternative perspective of complementing cognition and affect Presents a comprehensive collection of values and valuing in mathematics education